No longer at ease - Achebe, Chinua, 1930- (New York : Ballantine Books, 1984)
After returning to Africa from his education abroad, Obi Okonkwo feels alienated and disgusted at the fact that he has been thrust into the ruling class, of whom most are corrupt.
Keywords: City and town life -- Nigeria -- Lagos -- Fiction; Igbo (African people) -- Fiction; Lagos (Nigeria) -- Fiction; Nigeria -- Fiction